Designing children’s artwork performance model for primary school environment in Malaysia / Tun Mohd Irfan Mohd Suria Affandi ... [et al.] - Mohd Suria Affandi, Tun Mohd Irfan; Said, Ismail; Fazwan, Azrul; Rasidi, Hisyam; Za’bar, Zarina (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
In Malaysia, many parents encourage their children to pursue science stream rather than art. They perceive that those who study science holds a brighter future in securing a well paying job. Arts has always been a marginalised subject taught in school to be creative. Unfortunately, creativity is not applied to how they think. Children’s artwork performance in general affects their cognitive, psychological, behavioral and social development. The aim of this research is to understand children’s perspective towards art and art-making. Here, the main objective is to identify the best model to represent the contributing factors that influence artwork performance among school children at Malaysian primary school. Data was collected using a survey questionnaire. Utilizing a convenience sampling method, 110 students from SK Taman Bukit Indah, Johor Baharu were chosen. Multiple linear regression technique was the analysis adapted in order to achieve the research objective. This research is significant towards identifying the most significant factors which influence children’s participation in art-making. In the near future, the research will be extended to the secondary school children in Malaysia, and fair comparisons will be made within different streams.